Determinación de una metodología para la estimación de la vida útil ponderada de viviendas en Paraguay - Vazquez, V.; Lird, D. (Revista ALCONPAT, 2013)
Today the concept of Service Life is used widely around the world, and that the intention of building professionals is to implement projects that have a long service life to meet the purposes set out below certain levels of preventive maintenance. In other countries for almost two decades, investigations have been conducted on the durability and service life of materials and applied to buildings as a whole to determine which are the problems encountered, and so to project works far more effective and sustainable over time. The present work aims to determine a methodology applicable to Paraguay in order to estimate the useful life of the housing using the weighted method as articulating axis of the study. Keywords: Life pan, weighting, senavitat, carbonation, factor method.